Witzenhausen (Karakul Circulations: Colonial Economies and the Un_Making of Disciplinary Knowledges in Germany and Namibia, 2021)
104 JPEG files documenting project team trip to the archive of the Kolonialschule Witzenhausen
Keywords: History; Germany